ANTIFUNGAL AND ANTIBACTERIAL ACTIVITY OF PADDY-FIELDS CYANOBACTERIA FROM THE NORTH OF IRAN (Journal of Sciences, Islamic Republic of Iran)
Antifungal and antibacterial activity of some heterocystous cyanobacteria from paddy-fields in the north of Iran was studied. Soil samples were collected from paddy-fields of Gillan, Mazandaran and Golestan Provinces and cyanobacteria were isolated. Supernatants, methanolic and hexane extracts from biomass of 150 strains of cyanobacteria were isolated and screened against six strains of bacteria and eight strains of fungi. Methanolic extracts and culture supernatants of 21 strains of cyanobacteria exhibited significant antibacterial effect and 13 strains showed antifungal effect. No antimicrobial activity was detected in the hexane extracts and no extract inhibited the growth of E. coli. According to these results, it is concluded that strains of Stigonemataceae including Fischerella and Stigonema species, seem to be more potential for producing antimicrobial substances than other strains.